Gambaran Asupan Makanan dan Aktivitas Fisik dengan Status Gizi Remaja di SMP Swasta Santo Petrus Medan Tahun 2024 - Mutiara Silaban; Magda Siringo-Ringo; Indra Hizkia Perangin-Angin; Rusmauli Lumban Gaol (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Nutritional status influences various factors related to health, knowledge, economy, environment and culture. Nutritional problems arise because of an imbalance between physical activity and adolescent nutritional intake. Nutritional problems in adolescents can affect psychological performance, productivity and achievement. The impact is in accordance with nutritional status, namely poor nutritional status raises the risk of infectious diseases, whereas overnutrition and obesity raise the risk of various degenerative diseases. Food intake is the variety of food and drink the body needs at any time. Physical activity is any activity carried out because of business needs. Nutritional status is the final balance of nutritional intake in physical condition and food intake. Objective: Research to determine food intake and physical activity with nutritional status. Method: This research is a descriptive design using a simple random sampling method with a population of 258 respondents and a sample of 72 respondents. This research instrument uses a food recall questionnaire, activity recall and BMI measurement. Results: research shows that 53 respondents (73.6%) lack energy. 60 respondents (83.3%) lack carbohydrates. Protein is more 44 respondents (61.1%). 40 respondents (55.6%) lack fat. Vitamins are more than 46 respondents (63.9%). 59 respondents (81.9%) lack minerals. Lack of water for 72 respondents (100%). Light physical activity 70 respondents (97.2%). Underweight nutritional status of 52 respondents (72.2%). Conclusion: Based on the research results, it is found that the majority of students have poor food intake and physical activity with the nutritional status of teenagers. Researchers urge people to pay more attention to healthy food intake, sufficient activity and good nutritional status.